Teacher Perceptions of Administrative Support in Urban Charter Schools - (:unkn) unknown (My University, 2016)
National teacher survey results indicate that lack of administrative support is the most frequently cited reason as to why teachers leave charter schools. This non-experimental quantitative study explored what types of administrative support are more valuable to urban charter school teachers and the extent of that support in their current schools. This study also investigated if perceived needs of urban charter school teachers for administrative support change as they gain more teaching experience. In this study, a 41-item survey titled Dimensions of Administrative Support Survey was validated, and used to measure perceived support needs of 1,945 teachers from 127 different urban charter schools across the nation. Data analysis involved various quantitative methods including factor analysis, descriptive statistics, one sample t-test, and one-way ANOVA. Three themes emerged from the analysis of data: Perceived Importance of Administrative Support: (a) except for emotional support, all dimensions of administrative support are more important to first year teachers in urban charter schools than teachers with more experience, and the importance of administrative support gradually decreases as teachers gain more teaching experience; (b) urban charter school teachers in career stage-I and career stage-II have significantly higher perceived need for appraisal and informational support compared to teachers in career stage-III; (c) instrumental and emotional support are more important to urban charter school teachers than other dimensions of support, where informational support ranks last in importance. Perceived Administrative Support Gap (PASG): (a) there is a statistically significant difference between teachers’ perceived need for administrative support and the extent of such support in their current schools, confirming that urban charter school teachers are not satisfied with the level of support that they receive; (b) urban charter school teachers in their first to fourth years of teaching are more concerned about the extent of administrative support than teachers with more experience. Level of Experience and Teacher Turnover: (a) urban charter school teachers are considerably younger and with less teaching experience than teachers in traditional public schools and charter schools at large; and (b) the average teacher turnover rate in urban charter schools is about 39%.
Keywords: Administrative Support; Charter Schools; Principal Support; Teacher Retention; Teacher Turnover; Urban Public Schools